Larvicidal Activity of Bunium persicum Essential Oil and Extract against Malaria Vector, Anopheles stephensi - Hassan Vatandoost; Arezoo Rustaie; Zeynab Talaeian; Mohammad Reza Abai; Fatemeh Moradkhani; Mahdi Vazirian; Abbas Hadjiakhoondi; Mohammad Reza Shams-Ardekani; Mahnaz Khanavi (Tehran University of Medical Sciences, 2018)
Background: Malaria, a mosquito-transmitted disease, is still a major human health problem all over the world. Larviciding is a component of comprehensive control program to overcome the disease. Negative aspects of synthetic insecticides application, such as environmental safety concerns, have favored use of natural insecticides. Methods: Larvicidal activity of essential oil, extracts and fractions of a wild grown and a cultivated type of Bunium persicum fruits against malaria vector Anopheles stephensi was assessed according to the method described by WHO. Results: Bunium persicum showed remarkable potency against An. stephensi larvae. LC50 values for essential oil, total extract, petroleum ether fraction and methanol fraction were 27.4284, 64.9933, 85.9933 and 255.7486ppm for wild type, and 21.3823, 63.2580, 62.7814 and 152.6357ppm for cultivated one. Conclusion: The results of this study suggest B. persicum as a valuable source of natural insecticides against malaria vector Anopheles stephensi.